Recovery from drought: Viability and hatching patterns of hydrated and desiccated zooplankton resting eggs. Issue 1 (7th March 2019) - Vargas, Anderson L.; Santangelo, Jayme M.; Bozelli, Reinaldo L.
Abstract: Many zooplankton organisms produce resting eggs before harsh environmental conditions. After aquatic systems are recovered, animals hatch from resting eggs and help re‐establish active communities. However, although the ability of resting eggs to survive desiccation is largely known, it is unclear to what extent the duration of desiccation affects the viability and hatching patterns of resting eggs. In this study, we assessed the viability of resting egg banks in naturally wet and dry sediments through ex‐situ hatching experiments. In addition, we simulated dry out episodes of different durations (2 and 8 months) in wet sediments originating from temporary systems. We observed hatchlings of rotifers, cladocerans, copepods, ostracods, and anostracans in wet and dry sediments. Drying the sediments for different durations did not change the species richness and composition of hatchlings, possibly because temporary systems select for species and genotypes that are more prone to producing resting eggs, which survive desiccation. However, some species were stimulated to hatch after desiccation, suggesting that desiccation might help break the dormancy of resting eggs from temporary systems. Desiccation intervals up to 8 months likely do not affect the viability of resting eggs from temporary systems. Since many lakes are about to experience unpredictable droughts owing to human activities and ongoing global changes, the ability of resting eggs to tolerate desiccation will play a key role in zooplankton community recovery.